Creating Markets in Ethiopia : Sustaining Progress Towards Industrialization - World Bank; International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Ethiopia has made impressive strides along its developmental path. Job creation is now the critical development challenge, raising the importance of the private sector agenda. After more than a decade of sustained public sector-led growth, the government is revising its growth strategy to allow for a much greater role for the private sector in driving growth and job creation. Broadening the base for job creation beyond light manufacturing toward a wider range of high productivity agricultural and services activities will help to overcome the uneven spatial distribution of manufacturing jobs across the country. Ethiopia has a number of advantages that it can leverage to attract the investment needed for job creation. These include rapidly improving transport and energy infrastructure, low labor costs, a large and growing domestic market, cheap power, an ideal climate, and preferential market access to the European Union, the United States, and other major markets. The purpose of the Ethiopia country private sector diagnostic (CPSD) is to support the transition to a private sector- driven growth model that advances the country’s development objectives and, in particular, delivers the necessary jobs. It identifies investment opportunities that can materialize in the short term, and the reforms that are needed to enable these opportunities to emerge. It also discusses how specific actions by the public sector, in collaboration with the private sector, in filling gaps in public investment, reforming business regulations and trade policy, addressing market failures, and enhancing the efficiency of key backbone services and sectors, while tackling gender inequalities, can fully unleash the potential of private sector investment.